2018
DOI: 10.22492/ije.6.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Service Elementary Teachers’ Scientific Literacy and Self-Efficacy in Teaching Science

Abstract: Many educators and educational institutions worldwide have agreed that the main goal of science education is to produce a scientifically literate community. Science teachers are key to the achievement of scientific literacy at all levels of education because of the essential role they play in preparing scientifically literate individuals. Studies show that pre-service elementary teachers need to build more confidence in teaching science and scientific literacy during their teacher education programs in order f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
5
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 27 publications
3
33
5
8
Order By: Relevance
“…Additionally, although we found few difference in respondents' knowledge about life science, Earth science and physical science, other researchers found that most teachers had the highest self-efficacy in teaching biology and the lowest self-efficacy in teaching physics (Al Sultan et al, 2018). Similarly, Burgoon et al (2011) found that students and teachers have the most misconceptions in the physical sciences.…”
Section: Discussioncontrasting
confidence: 44%
See 2 more Smart Citations
“…Additionally, although we found few difference in respondents' knowledge about life science, Earth science and physical science, other researchers found that most teachers had the highest self-efficacy in teaching biology and the lowest self-efficacy in teaching physics (Al Sultan et al, 2018). Similarly, Burgoon et al (2011) found that students and teachers have the most misconceptions in the physical sciences.…”
Section: Discussioncontrasting
confidence: 44%
“…Science teachers play an essential role in educating society about how the world works. Al Sultan et al (2018) argued that pre-service teachers enter the teaching field with low selfefficacy beliefs. In their study, 49 pre-service elementary teachers in an introductory or advanced science methods course completed a survey assessing their scientific background.…”
Section: Science Teaching Self-efficacy Of Pre-service Teachersmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results of the research, the researcher argued about the need for efforts to improve scientific literacy skills. One way that physics teachers can do is the application of scientific literacy in learning is needed to prepare students who are literate (Sultan et al 2018). The implication of this scientific literacy results in the next research will be applied in making learning plans.…”
Section: Resultsmentioning
confidence: 99%
“…Keharusan guru dan calon guru SD memiliki kemampuan literasi sains yang baik juga dijelaskan oleh Sultan, A., dkk. bahwa it is critical for pre service elementary teachers to havehigh levels of scientific literacy and confidence in teaching science therefore, universities are encouraged to help their student gain abilities and knowledge that will help them achieve this goal Sultan et al (2018) .…”
mentioning
confidence: 99%